ОИЛАДАГИ МАЪНАВИЙ МУҲИТДА ОТА-ОНА ИБРАТИ – ЖАМИЯТ ТАРАҚҚИЁТИ ОМИЛИ (Scientific journal of the Fergana State University, 2023)
The  parents’ role and  place  in  upbringing  and  education  of  the  youth  are  considered  in  this article.